Ultrastructural Study of Long-Term Measles Infection in Cultures of Hamster Dorsal-Root Ganglion - Raine, Cedric S. (1971)
The morphogenesis of the Edmonston strain of measles is described in cultures of hamster dorsal-root ganglion maintained for as long as 63 days postinoculation. The patterns observed confirmed those previously reported in both neural and non-neural tissue. However, in the present tissue, the development of viral material could be followed chronologically within different cell types such as neurons and Schwann cells. Active replication was visualized up to 63 days postinoculation. The appearance of cytoplasmic nucleocapsid preceded that of intranuclear nucleocapsid, the latter occurring after 14 days. These intranuclear inclusions were formed after the transformation of the nucleoli into bizarre pleomorphic bodies which eventually segregated into clumps of nucleocapsid. These intranuclear inclusions mimic those seen in subacute sclerosing panencephalitis, now known to be etiologically related to a measles-like virus.